BACTERIAL INFECTIONS-INDUCED ORAL ERYTHEMA MULTIFORME IN A SEPTIC CHILD: A RARE CASE REPORT - Amira Shafuria; Riani Setiadhi (FKG Unlam, 2023)
Background: Sepsis is a medical emergency condition that triggers an immune response due to an infectious process. Causative organisms in sepsis including viruses, bacteria, fungi, and parasites. Microorganism infection is one of the etiologies of erythema multiforme. Objective: This case report was aimed to describe the bacterial infection as a trigger for oral erythema multiforme in a septic child. Case: A 12-years-old boy was referred to the Oral Medicine Department. Extraoral showed a symmetric face and he was using a nasogastric tube. There were erosive lesions and tend to bleed, hemorrhagic crusts on the upper and lower lips. Laboratory test results revealed increasing in leukocyte (15,880/µL), procalcitonin (24.58 ng/mL), and C-reactive protein (3.67 mg/L). The identified microorganisms in pus specimens including gram-positive coccus and gram-negative rods as well as the isolated bacterial colonies were Enterococcus faecalis, Klebsiella pneumoniae, and Citrobacter koseri. The diagnosis was oral erythema multiforme induced by bacterial infections. Case management: The medications given by the Pediatric Department were cefotaxime vial 1 gram, metronidazole 500 mg/100 ml, and paracetamol 1 gr/100 ml. The Oral Medicine Department gave the instructions for compressing the lips with gauze soaked in 0.9% Sodium Chloride solution four times a day to remove crusts and accelerate wound healing. Oral lesions showed significant improvement after 7 days of therapy. Conclusion: Oral erythema multiforme in a pediatric patient could be induced by sepsis of bacterial infection. The microbial infection causes the release of endotoxins that trigger erythema multiforme. Keywords: Bacterial infection, Oral erythema multiforme, Sepsis.